A Study of Innovation Factors Affecting Organisational Performance - Shamma Ebraheem Esmaeel Saleh Alhosani; Edie Ezwan Mohd Safian (International Journal of Sustainable Construction Engineering and Technology, 2024)
This study aimed to develop a multi-linear regression model to explore the impact of innovation factors on the organizational performance of ADNOC. It employed a quantitative research approach in collecting and analysing the numerical data statistically. Correlation results found that there are significant positive relationships between all constructs, indicating that as one variable increases, the other tends to increase as well in the interconnections among marketing, management, process, organization structure, and organizational performance within the studied context.  While, for the multi-linear regression model, it was found that the correlation coefficient of 0.503 between the predictors and the dependent variable, indicating a strong relationship. Furthermore, with the coefficient of determination, it suggests that 50.3% of the selected independent variables collectively explain the variance in the dependent variable. This equation model can be directly applied to ADNOC's organizational performance by inputting the values of the innovation factors/variables into the equation. The established equation holds potential benefits for organizations aiming to enhance performance through the application of innovative strategies.